Persepsi Tentang Pembelajaran Daring dan Hasil Belajar Mahasiswa Keperawatan - Christa Vike Lotulung; I Gede Purnawinadi (NUTRIX, 2023)
The COVID-19 pandemic has had a very significant impact on the world of education. The learning process is required to be carried out online because of restrictions on activities and community activities in an effort to prevent transmission and infection of the corona virus. This study aims to analyze the relationship between student perceptions of online learning and learning outcomes. The quantitative method with a cross-sectional approach was carried out by researchers and used a total sampling technique to collect data from respondents. Data were analyzed univariately and bivariately using Spearman Rank. The results of the study showed that perceptions of online learning by nursing students were dominant in the negative category, while student learning outcomes were in the good category. There is no significant relationship between perceptions of online learning and student learning outcomes. It is hoped that educational institutions will continue to maintain quality online learning facilities in supporting the achievement of good learning outcomes. Future research can explore other factors that influence the learning outcomes of nursing students who do online learning Abstrak Pandemi COVID-19 memberikan dampak yang sangat signifikan dalam dunia pendidikan. Proses pembelajaran dituntut harus dilakukan secara daring karena pembatasan kegiatan dan aktifitas masyarakat dalam upaya mencegah penularan dan infeksi virus corona. Penelitian ini bertujuan untuk menganalisis hubungan persepsi mahasiswa tentang pembelajaran daring dnegan hasil belajar. Metode kuantitatif dengan pendekatan cross-sectional dilakukan peneliti dan menggunakan teknik total sampling dalam mengumpulkan data dari responden. Data dianalisis secara univariat dan bivariat menggunakan Spearman Rank. Hasil penelitian menunjukkan bahwa persepsi pembelajaran daring mahasiswa keperawatan dominan dalam kategoiri negatif sedangkan hasil belajar mahasiswa dalam kategori baik. Tidak terdapat hubungan yang bermakna antara persepsi pembelajaran daring dengan hasil belajar mahasiswa. Diharapkan institusi pendidikan tetap mempertahankan fasilitas pembelajaran daring yang berkualitas dalam menunjang capaian hasil belajar yang baik. Penelitian selanjutnya dapat mengeksplorasi faktor-faktor lain yang mempengaruhi hasil belajar mahasiswa keperawatan yang melakukan pembelajaran secara daring. Kata kunci : Hasil belajar, Pembelajaran daring, Persepsi